Kontrreformacja? Modele dystrybucji filmowej w Polsce w pierwszych latach postpandemicznych - Adamczak, Marcin; Orankiewicz, Agnieszka (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2026)
The article examines the transformations in distribution models prompted by the rise of streaming platforms. It identifies three new models that have emerged in the post-2020 market landscape in response to the expansion of streaming: the production (corporate) model, the production-executive (streaming) model, and the hybrid model, all of which coexist with the redefined traditional model 2.0. These models represent attempts to balance the interests of theatrical exhibitors and distributors, and those of streaming platforms, reflecting a broader recalibration of business strategies in light of shifting industry dynamics. The second part of the article investigates how the models identified between 2020 and 2022 have evolved in the market context since 2022. Several adjustments observed during this period collectively suggest a partial reversion to pre-pandemic distribution relations, a trend the article considers to be a ‘counter-reformation’. Nevertheless, the conclusions underscore that this movement does not negate the transformative impact of the streaming-driven ‘reformation’ of the theatrical distribution landscape.